Management of common surgical complications. Issue 2 (February 2023) - Skervin, Alicia; Levy, Bruce
Abstract: No surgery is ever free of the risk of a complication. As the number of surgeries increase annually, the incidence of complications is expected to rise proportionally. Surgical complications are associated with significant physiological and psychological morbidity and mortality. While there are generic complications that affect all types of surgery, each specific type of surgery in addition carries its own speciality-specific complications. General complications like pain, bleeding, atelectasis, infection and venous thromboembolism are just a few that can complicate the postoperative recovery phase. It cannot be overemphasized that the key to managing surgical complications is preventing them from manifesting in the first place. Preoperative assessment clinics and the implementation of the WHO checklist have allowed the identification and optimization of risk factors. This article explores the prevention and management of common surgical complications which a junior surgical trainee is likely to face.